Establishing tungsten carbides as active catalysts for CO2 hydrogenation. Issue 44 (24th October 2022) - Juneau, Mitchell; Yaffe, Daphna; Liu, Renjie; Agwara, Jane N.; Porosoff, Marc D.
Abstract : Tungsten nanoparticles are encapsulated in silica, preserving particle size during carburization, leading to active and selective catalysts for CO2 hydrogenation. Abstract : Molybdenum carbides are promising catalysts for the reverse water–gas shift (RWGS) reaction, and we aim to understand if similar performance can be observed across the library of transition metal carbides. Although tungsten and molybdenum carbides exhibit similar catalytic properties for hydrogenation reactions, tungsten carbide has not been thoroughly evaluated for CO2 hydrogenation. We hypothesize that the extreme synthesis conditions necessary for carburizing tungsten can cause sintering, agglomeration, and carbon deposition, leading to difficulty evaluating the intrinsic activity of tungsten carbides. In this work, tungsten is encapsulated in silica to preserve particle size and demonstrate correlations between the active phase composition and RWGS performance.